INCREASING STUDENTS’ VOCABULARY BY USING BIMODAL SUBTITLING IN SHORT MOVIE - Hoogendyk, Fika Widya Christy; Arifin, Zainal; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research aims to know whether the use of Bimodal Subtitling in short movie can increase students’ vocabulary in learning English. The method that is used to collect the data is Pre-Experimental. The researcher took 8H which consist of 29 students as the sample. Based on the data, the researcher found out that the students’ mean score of pre-test is 57.24 while the students’ mean score of post-test is 81.90. The students’ development in increasing vocabulary during the research showed a good change. It was found from the result of t-test that t-value is higher than t-table (13.05 > 2.048). Based on that, it can be concluded that the use of Bimodal Subtitling media in short movie can increase students’ English vocabulary.   Keywords: Bimodal Subtitling, short movie, vocabulary   Abstrak: Penelitian ini bertujuan untuk mengetahui apakah penggunaan media Bimodal Subtitling dalam film pendek dapat menambah kosakata siswa dalam belajar bahasa Inggris. Metode yang digunakan untuk mengumpulkan data adalah Pre-Experimental. Peneliti mengambil kelas 8H yang berjumlah 29 siswa sebagai sampel. Berdasarkan data, nilai rata-rata siswa pada pre-test adalah 57.24 sedangkan nilai rata-rata siswa pada post-test adalah 81.90. Perkembangan siswa dalam menambah kosakata selama penelitian berlangsung menunjukan perubahan yang baik, hal ini dibuktikan dengan menggunakan rumus t-test yang menunjukkan bahwa t-value lebih besar dari t-table (13.05 > 2.048). Berdasarkan hasil dari penelitian ini, dapat disimpulkan bahwa penggunaan media Bimodal Subtitling dalam film pendek mempengaruhi pencapaian siswa dalam menambah kosakata bahasa Inggris.   Kata kunci: Bimodal Subtitling, film pendek, kosakata